Diagnostic utility of cardiac troponin T level in patients with cardiac amyloidosis. (4th September 2017) - Takashio, Seiji; Yamamuro, Megumi; Izumiya, Yasuhiro; Hirakawa, Kyoko; Marume, Kyohei; Yamamoto, Masahiro; Ueda, Mitsuharu; Yamashita, Taro; Ishibashi‐Ueda, Hatsue; Yasuda, Satoshi; Ogawa, Hisao; Ando, Yukio; et al.
Abstract: Aim: The aim of this study was to evaluate the diagnostic utility of high‐sensitivity cardiac troponin T (hs‐cTnT) levels in discriminating cardiac amyloidosis from patients with cardiac hypertrophy caused by aetiologies other than cardiac amyloidosis. Methods and results: Serum hs‐cTnT levels were measured in 96 patients with cardiac amyloidosis (light chain: 23, wild‐type transthyretin amyloidosis: 40, and mutated transthyretin amyloidosis: 33), and 91 patients with other causes of cardiac hypertrophy who were confirmed to have no cardiac amyloidosis by endomyocardial biopsy (control group). The diagnostic utility and cut‐off value of hs‐cTnT were evaluated by receiver operating characteristic analysis. The median hs‐cTnT levels were higher in cardiac amyloidosis than the control group [0.048 (0.029–0.073) vs. 0.016 (0.010–0.031) ng/mL; P  < 0.001]. High levels of hs‐cTnT were suggestive of cardiac amyloidosis (cut‐off value: 0.0312 ng/mL, sensitivity: 0.74, specificity: 0.76, area under the curve: 0.788; 95% confidence interval: 0.723–0.854, P  < 0.001), compared with brain natriuretic peptide and E/e′ ratio. The hs‐cTnT levels were also useful in differentiating each type of amyloidosis from the control group. Multivariate analysis identified log hs‐cTnT as an independent diagnostic factor for cardiac amyloidosis (odds ratio: 2.22; 95% confidence interval: 1.30–3.80; P  = 0.004). Conclusions: High serum levels of hs‐cTnT are highly suggestive of cardiac amyloidosis, allowing its differentiation from cardiac hypertrophy of other aetiologies. Further refined diagnostic approaches that include imaging modalities and histopathological examination are needed for these patients to avoid underdiagnosis of cardiac amyloidosis.